MENINGKATKAN HASIL BELAJAR IPA MELALUI MEDIA GAMBAR PADA SISWA KELAS IIA SDN 78 PEKANBARU - Seriani Panjaitan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
Natural Sciences (IPA) is one of the important lesson in learning. Even for the upper secondary level or high school level, this subject to one program penjurusan which will determine the students majoring in College. In addition, this science subjects also joined the national final examination (UAN) who became the main requirements for students graduating. The research design used in this research is the class action research (PKT). The aspect that is observed on each cycle and is the result of the learning and teaching processsubjects source of energy and its benefits using media pictures. The subject of the learning improvement activities are the students of class 2 SDN 78 Pekanbaru with the number of students 39 people with the details of 20 students of male and female students 19 people. The results of research on the pre cycle, the value of the results of the learning science students, the average 43,08 and there are no students who achieve KKM. Then on the cycle I the results of learning science students an average of 1.807 and students who achieve KKM 9 students (23%). At cycle II, the value of the average student learning results reach 82,56 and students who achieve KKM 39 students (100%). The implementation of the media image can improve the results of learning science students on the subjects of energy sources and benefits. The learning process explains the source of energy and its benefits the sequence on each cycle apply media image and be led by the researchers and observers.